Surveillance, Epidemiology, and Estimated Burden of Neonatal Abstinence Syndrome, Tennessee, 2013-2016. (September 2019) - Brennan, Julia; Wiedeman, Caleb; Dunn, John R.; Schaffner, William; Jones, Timothy F.
Objectives: Between 2003 and 2013, the rate of neonatal abstinence syndrome (NAS)—a postnatal drug withdrawal syndrome—in Tennessee increased approximately 10-fold. NAS surveillance is relatively new, and underestimation associated with surveillance has not been described. We compared data from the Tennessee NAS public health surveillance system (TNSS) with a second source of NAS data, hospital discharge data system (HDDS), and estimated the true number of infants with NAS using capture-recapture methods. Methods: We obtained NAS data on cases of NAS among Tennessee infants from TNSS and HDDS from January 1, 2013, through December 31, 2016. We matched cases of NAS identified in TNSS to cases identified in HDDS. We estimated the true number of infants with NAS by using the Lincoln-Peterson estimator capture-recapture methodology. Results: During the study period, 4070 infants with NAS were reported to TNSS, and 5321 infants with NAS were identified in HDDS; 2757 were in both data sets. Using capture-recapture methods, the total estimated number of infants with NAS during the study period was 7855 (annual mean = 1972; estimated range = 1531-2427), which was 93% more than in TNSS and 48% more than in HDDS. Drugs used for the medication-assisted treatment of substance use disorder were the most commonly reported substances associated with NAS (n = 2389, 59%). Conclusions: TNSS underestimated the total burden of NAS based on the capture-recapture estimate. Case-based public health surveillance is important for monitoring the burden of and risk factors for NAS and helping guide public health interventions.